2013
DOI: 10.1161/atvbaha.113.301714
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Dimethylglycine and Risk of Incident Acute Myocardial Infarction in Patients With Stable Angina Pectoris

Abstract: Objective— Dimethylglycine is linked to lipid metabolism, and increased plasma levels may be associated with adverse prognosis in patients with coronary artery disease. We evaluated the relationship between plasma dimethylglycine and risk of incident acute myocardial infarction in a large prospective cohort of patients with stable angina pectoris, of whom approximately two thirds were participants in a B-vitamin intervention trial. Model discrimination and reclassification when adding plasma dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 38 publications
(17 reference statements)
2
37
0
Order By: Relevance
“…A detailed description of the study population has been published previously 13. In brief, 4164 patients who underwent coronary angiography for suspected stable angina pectoris at Haukeland and Stavanger University Hospitals in Western Norway during 2000–2004 were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the study population has been published previously 13. In brief, 4164 patients who underwent coronary angiography for suspected stable angina pectoris at Haukeland and Stavanger University Hospitals in Western Norway during 2000–2004 were included.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity was identified as having body mass index ≥30 kg/m 2 . Current smokers were defined as those who reported currently smoking, those who quit smoking within <1 month preceding examination, or having serum cotinine levels ≥85 nmol/L at baseline 13. Diabetes mellitus included types 1 and 2 and was classified according to previous diagnosis or by having plasma fasting glucose >7 mmol/L, nonfasting glucose >11.1 mmol/L, or a single measurement of glycated hemoglobin >6.5% 17.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No associations of dietary choline and betaine with cardiovascular disease (CVD) risk have been reported,7, 8, 9 whereas circulating choline and its metabolites have been associated with lifestyle diseases including atherosclerotic cardiovascular disease 4, 6, 10, 11. However, less attention has been paid to the possible associations between choline metabolites and cardiac arrhythmias, although a recent metabolomics study suggested no significant association between plasma betaine and incident AF in the population‐based Framingham Study 12…”
mentioning
confidence: 99%